2002
DOI: 10.1523/jneurosci.22-06-02035.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Apoptosis Inhibitory Protein Is a Direct Inhibitor of Caspases 3 and 7

Abstract: The neuronal apoptosis inhibitory protein (NAIP) was identified as a candidate gene for the inherited neurodegenerative disorder spinal muscular atrophy. NAIP is the founding member of a human protein family that is characterized by highly conserved N-terminal motifs called baculovirus inhibitor of apoptosis repeats (BIR). Five members of the human family of inhibitor of apoptosis proteins including NAIP have been shown to be antiapoptotic in various systems. To date, a mechanism for the antiapoptotic effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 45 publications
2
111
0
Order By: Relevance
“…The pattern of neuronal loss in SMA is consistent with the distribution of the NAIP protein within the central nervous system . Finally, NAIP's capacity to suppress cell death is compatible with its deletion playing a role in determining cell loss (Liston et al, 1996;Xu et al, 1997;Maier et al, 2002).…”
Section: Iap Gene Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of neuronal loss in SMA is consistent with the distribution of the NAIP protein within the central nervous system . Finally, NAIP's capacity to suppress cell death is compatible with its deletion playing a role in determining cell loss (Liston et al, 1996;Xu et al, 1997;Maier et al, 2002).…”
Section: Iap Gene Familymentioning
confidence: 99%
“…It was subsequently shown that the IAPs could directly inhibit the activity of several recombinant caspases in vitro Roy et al, 1997;Maier et al, 2002), and that isolated BIR domains possessed this activity (Takahashi et al, 1998). The BIR domains of the IAPs are the most fully characterized functional units of the IAPs.…”
Section: Iap Bir Domains Bind and Inhibit Caspasesmentioning
confidence: 99%
“…(28)(29)(30). At the caspase level, inhibitor of apoptosis protein (IAP) family members [c-IAP1, c-IAP2, survivin, NIAP, and X-linked IAP (XIAP)] can bind to caspase-9, caspase-7, and caspase-3 and prevent the activation of the caspase cascade (31)(32)(33)(34)(35). Among these IAP members, XIAP seems to be the most potent direct caspase inhibitor (31,34) and has been shown to be overexpressed in tumor cells (36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show direct binding and inhibition of caspase-3 and -9 (Maier et al, 2002;Davoodi et al, 2004Davoodi et al, , 2010, but others do not (Roy et al, 1997). Also, NAIPs lack certain caspase-interaction residues within the BIR domains that would be necessary for direct inhibition of caspases, raising concern about whether NAIP can inhibit caspases in physiological settings (Scott et al, 2005;.…”
mentioning
confidence: 99%